Effect of Feeding Distiller’s Dried Grains with Solubles (DDGS) and Legume Roughage on Serum Biochemical Profile in HF x Kankrej Crossbred Heifers - Dhami, Arjan J; Patel, Dignesh K; Chaudhari, Dinesh V; Pandey, Manish; Lunagariya, Pravin M; Shah, Shailesh V (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The study was undertaken on HF x K heifers (n=24) to evaluate the effect of feeding rice distiller’s dried grains with soluble (RDDGS) and Soy DOC alone or in combination with cereal and/or legume straws as TMR from an average 8 months till 19 months of age on their health and serum biochemical profile. Heifers were uniformly distributed into three treatment groups. Further, each treatment group was subdivided into two roughage groups and were fed TMR having 50% concentrate and 50% roughage. The concentrates contain 0+40, 20+20, and 40+0% combination of RDDGS + Soy DOC, respectively in T1, T2, and T3 treatment. Each treatment was further subdivided to fed roughage as 50% wheat straw (R1) and another half as a mixture of wheat straw and groundnut gotar (R2). Heifers were also offered green hybrid Napier @ 2 kg/h/d up to 100 kg b.wt. and 4 kg/h/d for above 100 kg b.wt and Chelated Mineral Mixture @ 35 g/animal/d. Blood samples were collected in clot activator vials by jugular vein puncture from experimental heifers at the start and then at every month and serum was stored at -20°C till analysis. The collected serum samples were analyzed for biochemical constituents using suitable Coral and/or Tulip diagnostic kits on a chemistry analyzer. The data obtained were analyzed by 3 factors’ factorial RBD. The results revealed that inclusion of RDDGS in concentrate and feeding a mixture of legume and cereal straws did not adversely affect the blood biochemical parameters, like glucose, total protein, albumin, globulin, cholesterol, BUN, and minerals calcium and phosphorus, all were within normal physiological limits. However, significantly reduced serum urea level and increased cholesterol levels on feeding RDDGS suggested it a good source of rumen degradable protein and fat enhancing steroidogenic function. Serum albumin, globulin, A:G ratio and minerals of heifers were within normal limit indicating no harmful effect of feeding RDDGS and mixture of groundnut straw and wheat straw on kidney and liver function. Thus, it can be concluded that feeding RDDGS in place of soy DOC in concentrate and feeding a mixture of groundnut gotar and wheat straw to growing crossbred heifers from 8 months till puberty/19 months maintains normal growth rate without adverse effect on the health and blood biochemical profile.